Disease outbreak accompanies the dispersive structure of shrimp gut bacterial community with a simple core microbiota - Yao, Zhiyuan; Yang, Kunjie; Huang, Lei; Huang, Xiaolin; Qiuqian, Linglin; Wang, Kai; Zhang, Demin (AMB Express, 2018)
Increasing evidence has emerged supporting a tight link between gut bacterial community and shrimp health. However, the knowledge about the variation of gut bacterial community, especially with different disease onset time, remains elusive. Here, healthy and diseased shrimps were collected at 3 disease-outbreak times (day 70, 80 and 85) to investigate the variation of gut bacterial community and its underlying ecological process with 16S rRNA gene amplicon sequencing. The gut bacterial community of diseased shrimp was distinct from the healthy one and temporally less stable, characterized by decreased alpha-diversity and dispersive structure. And its dominant ecological process experienced a transition with disease onset time, although deterministic process mainly governed the healthy gut bacterial assembly. In addition, the core microbiota of healthy shrimp gut harbored more diverse bacterial taxa with more cooperative interactions, while the diseased core microbiota showed opposite pattern with significantly higher abundance of opportunistic pathogens as well. These findings indicate that shrimp heath is highly relevant to the homeostasis of its gut bacterial community. Preservation and restoration of the bacterial community equilibrium could represent an effective strategy for shrimp disease prevention.